Explaining ASEAN-3's Investment Puzzle A Tale of Two Sectors - Zhou, Yong Sarah (IMF Working Papers; Working Paper, 2013)
The prolonged investment decline in post-Asian crisis emerging Asia, in contrast to the swift recovery of economic growth, has remained a puzzle. This paper shows that the post-crisis investment recession has been mainly concentrated in the nontradable sector, and hypothesizes that the slowdown is because firms operating in that sector are financially constrained. Empirical results based on macro and firm-level data from Indonesia, Malaysia, and Thailand (ASEAN-3) support this hypothesis.